2019
DOI: 10.1101/543959
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Frequent expansion of Plasmodium vivax Duffy Binding Protein in Ethiopia and its epidemiological significance

Abstract: 28 Plasmodium vivax invasion of human erythrocytes depends on the Duffy Binding 29 Protein (PvDBP) which interacts with the Duffy antigen. PvDBP copy number varies 30 between P. vivax isolates, but the prevalence of PvDBP multiplications in Sub-Saharan 31 Africa and its impact are unknown. We determined the prevalence and type of PvDBP 32 duplications, as well as PvDBP copy number variation among 178 Ethiopian P. vivax 33 isolates using a PCR-based diagnostic method, a novel quantitative real-time PCR 34 assay… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
3

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 41 publications
(64 reference statements)
0
8
0
Order By: Relevance
“…However, it has now clearly been demonstrated that P. vivax is also able to infect individuals who are Duffy negative, lacking DARC expression on their red blood cell surface (21,22). This could indicate that P. vivax is able to utilize other ligands for invasion such as PvRBP2b (28) and erythrocyte binding protein 2 (ebp2) (30), although it is also possible that PvDBP is still involved in the invasion of Duffy negative cells (26). It is also worth noting that the genetic essentiality of PvDBP for parasite growth has never been able to be directly tested, as P. vivax cannot be cultured and therefore cannot be genetically manipulated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it has now clearly been demonstrated that P. vivax is also able to infect individuals who are Duffy negative, lacking DARC expression on their red blood cell surface (21,22). This could indicate that P. vivax is able to utilize other ligands for invasion such as PvRBP2b (28) and erythrocyte binding protein 2 (ebp2) (30), although it is also possible that PvDBP is still involved in the invasion of Duffy negative cells (26). It is also worth noting that the genetic essentiality of PvDBP for parasite growth has never been able to be directly tested, as P. vivax cannot be cultured and therefore cannot be genetically manipulated.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has recently been shown that P. vivax is also able to infect individuals who are Duffy negative, so express little or no DARC on the surface of their erythrocytes (21)(22)(23)(24). While the invasion of Duffy negative erythrocytes could still rely on PvDBP (25,26), the sole focus on PvDBP as a vaccine candidate clearly needs to be reassessed and additional targets evaluated, either as potential substitutes for PvDBP, or to be used in combination with it. As noted above, erythrocyte invasion is a very complex process, and while the process is much less well-understood in P. vivax than it is in P.…”
Section: Introductionmentioning
confidence: 99%
“…A molecular epidemiology study conducted in Ethiopia observed that the proportion of parasites with PvDBP amplification was higher in individuals carrying the FY*A allele compared to individuals carrying the FY*B [ 51 ]. On the other hand, in Madagascar where both Duffy-negative and Duffy-positive individuals coexist, PvDBP amplification is not selected in response to the Duffy null homozygotes [ 52 ].…”
Section: Introductionmentioning
confidence: 99%
“…Complicating these scenarios further are additional facets of Pv biology—several cases of Pv infection have now been observed in Duffy-negative individuals, suggesting that the parasite might have evolved an alternative pathway that is independent of DARC–DBL interaction for invasion [ 44 – 52 ]. Studies from Malagasy, Colombia and Ethiopia have also suggested that Pv DBP gene copy variations in the field are evident and indicative of Pv evolution [ 53 – 55 ]. Therefore, the development of Pv DBL-based vaccine seems to be fraught with several challenges—and here we highlight further reasons for scepticism in this direction.…”
Section: Introductionmentioning
confidence: 99%